MEREDUKSI KECEMASAN DENGAN TEKNIK DESENSITISASI SISTEMATIS - Giri, Putu Agus Semara Putra (LPPM IKIP PGRI Bali, 2020)
Anxiety is one form of irrational thought manifestation in individuals and the manifestation of uncomfortable conditions experienced by individuals in facing a challenge. High anxiety in facing the exam is a dangerous problem for students, because it will greatly affect the achievement and formation of student personality. Thus this problem really needs to be addressed appropriately and correctly by using techniques that are appropriate to the characteristics of students' problems. Of the many existing counseling models, it is necessary to choose the right counseling model to reduce the level of student anxiety. Then the Systematic Desensitization Technique which is predicted can reduce the anxiety experienced by students in facing exams. The technique is one of the techniques in behavioral counseling using relaxation movements. It can be predicted thus because the systematic desensitization technique seeks to condition the individual to be fully relaxed, from uncomfortable to more calm and relaxed in the face of the test so as to avoid the tension in the body and mind which is one of the causes of anxiety.